Factors associated with the non-use of condoms by brazilian adolescents: a systematic review (Research, Society and Development, 2022)
Objective: to analyze the factors associated with the non-use of condoms by Brazilian adolescents. Methodology: This is a systematic review. Data collection took place in PubMed, Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature on Health Sciences (LILACS), through the Health Sciences Descriptors: “adolescents”, “condoms”, “sexually transmitted diseases”, “human immunodeficiency virus”, “HIV”, “Brazil”, “adolescent”, “condoms”, “Sexually Transmitted Diseases”, “Brazil” and registration terms. From these, 728 articles were found, being selected, after careful analysis, 27 studies. Results: the age range adopted was between 10 and 19 years old, with a sample ranging from a maximum of 100,962 to a minimum of 50 participants. With the main findings related to non-use of condoms, the following stand out: knowledge of correct use, lack of guidance, early sexual initiation, interference in pleasure, steady partner, having two or more sexual partners, being younger, low maternal and adolescent, lower socioeconomic level, having confidence in the partner, using alcohol, using licit or illicit drugs and being female. Conclusion: an identification of aspects of possibility of preservation for a broader view of reality and points of view of existing health policies and drivers associated with the vision of changing safer sexual behavior in changing sexual behavior and, consequently, promoting and reduction of health risks.